Perancangan Konseptual Aplikasi Enterprise Risk Management (ERM) Khusus Lembaga Filantropi Syariah - Hardiyanto, Yan; Gusti Oka Widana (ITB AAS INDONESIA Surakarta, 2025)
This study designs an Enterprise Risk Management (ERM) application tailored for Sharia Philanthropy Institutions (LFS), such as Zakat Management Organizations (LAZ), using a holistic qualitative approach that fully integrates Sharia principles (kaffah). It addresses complex risks in managing zakat, infak, sedekah, and waqf (ZISWAF) funds—covering operational, Sharia compliance, reputational, and fraud dimensions—which threaten institutional sustainability and public trust. By adapting the COSO ERM framework, the proposed model emphasizes core Islamic values of amanah and maslahah, supported by Key Risk Indicators (KRI) such as Allocation to Collection Ratio (ACR) and Rasio Hak Amil (RHA) as early fraud warning mechanisms. The Risk Management Information System (SIM-R) features functional modules for Sharia compliance verification, real-time fraud detection, and operational risk assessment using qualitative probability-impact matrices. Non-functional requirements include CIA Triad security, real-time performance, and adherence to POJK and ISO 27001 standards. Through in-depth literature review and content analysis, this study bridges research gaps in ERM models for non-profit Sharia institutions, offering theoretical contributions to Islamic economics and practical recommendations to strengthen transparency, accountability, and credibility of LFS in Indonesia. Keywords: ERM, Sharia Philanthropy, ZISWAF, Fraud Detection, SIM-R, Holistic Qualitative